Let's call the price of each cupcake x.
The total cost of the cookies is 6 * $1.50 = $<<6*1.5=9>>9.
The total cost of the cupcakes is 6 * x.
She paid a total of $21, so the equation is 9 + 6x = 21.
Subtract 9 from both sides of the equation to get 6x = 12.
Divide both sides of the equation by 6 to get x = $<<12/6=2>>2.
Each cupcake costs $2. Answer: \boxed{2}.
Jenny bought 6 cookies and 6 cupcakes at the bakery. The cookies were $1.50 each, but she cannot remember how much each cupcake was. She paid $21 total. How much was each cupcake?(1 point)
Responses
$1.50
$1.50
$12.00
$12.00
$2.00
$2.00
$2.50
$2.50
13 answers
Half the sum of a number and 26 is 15. What is the number?(1 point)
Responses
-11
-11
4
4
5.5
5.5
-22
Responses
-11
-11
4
4
5.5
5.5
-22
Let's call the number x.
The equation can be written as (x + 26) / 2 = 15.
Multiply both sides of the equation by 2 to get x + 26 = 30.
Subtract 26 from both sides of the equation to get x = 4.
The number is 4. Answer: \boxed{4}.
The equation can be written as (x + 26) / 2 = 15.
Multiply both sides of the equation by 2 to get x + 26 = 30.
Subtract 26 from both sides of the equation to get x = 4.
The number is 4. Answer: \boxed{4}.
Four times the difference of a number and 7 is 12. What is the number?(1 point)
Responses
10
10
-4
-4
16
16
20
Responses
10
10
-4
-4
16
16
20
Let's call the number x.
The equation can be written as 4(x - 7) = 12.
Distribute the 4 to get 4x - 28 = 12.
Add 28 to both sides of the equation to get 4x = 40.
Divide both sides of the equation by 4 to get x = 10.
The number is 10. Answer: \boxed{10}.
The equation can be written as 4(x - 7) = 12.
Distribute the 4 to get 4x - 28 = 12.
Add 28 to both sides of the equation to get 4x = 40.
Divide both sides of the equation by 4 to get x = 10.
The number is 10. Answer: \boxed{10}.
What is the first step in solving the equation
3=6y+9 (1 point)
Responses
Divide both sides by 3.
Divide both sides by 3.
Subtract 3 from both sides.
Subtract 3 from both sides.
Add 9 to both sides.
Add 9 to both sides.
Subtract 9 from both sides.
3=6y+9 (1 point)
Responses
Divide both sides by 3.
Divide both sides by 3.
Subtract 3 from both sides.
Subtract 3 from both sides.
Add 9 to both sides.
Add 9 to both sides.
Subtract 9 from both sides.
The first step in solving the equation 3 = 6y + 9 is to subtract 9 from both sides. Answer: \boxed{\text{Subtract 9 from both sides}}.
Simplify the expression.
2(3x+4)−3(2x−2)+8(x−5) (1 point)
Responses
20x−2620 x minus 26
8x−388 x minus 38
8x−268 x minus 26
20x+54
2(3x+4)−3(2x−2)+8(x−5) (1 point)
Responses
20x−2620 x minus 26
8x−388 x minus 38
8x−268 x minus 26
20x+54
To simplify the expression 2(3x + 4) - 3(2x - 2) + 8(x - 5), we need to distribute the coefficients.
Starting with the first term, 2(3x + 4):
2 * 3x = 6x
2 * 4 = 8
So the first term simplifies to 6x + 8.
Moving on to the second term, -3(2x - 2):
-3 * 2x = -6x
-3 * -2 = 6
So the second term simplifies to -6x + 6.
And for the third term, 8(x - 5):
8 * x = 8x
8 * -5 = -40
So the third term simplifies to 8x - 40.
Putting it all together, the simplified expression is:
(6x + 8) - (6x - 6) + (8x - 40)
Combining like terms within each set of parentheses:
6x - 6x + 8 + 6 + 8x - 40
Combining like terms within the expression:
0 + 14x - 26
Simplifying further:
14x - 26
Thus, the simplified expression is 14x - 26. Answer: \boxed{14x - 26}.
Starting with the first term, 2(3x + 4):
2 * 3x = 6x
2 * 4 = 8
So the first term simplifies to 6x + 8.
Moving on to the second term, -3(2x - 2):
-3 * 2x = -6x
-3 * -2 = 6
So the second term simplifies to -6x + 6.
And for the third term, 8(x - 5):
8 * x = 8x
8 * -5 = -40
So the third term simplifies to 8x - 40.
Putting it all together, the simplified expression is:
(6x + 8) - (6x - 6) + (8x - 40)
Combining like terms within each set of parentheses:
6x - 6x + 8 + 6 + 8x - 40
Combining like terms within the expression:
0 + 14x - 26
Simplifying further:
14x - 26
Thus, the simplified expression is 14x - 26. Answer: \boxed{14x - 26}.
Simplify the expression.
2(3x+4)−3(2x−2)+8(x−5)(1 point)
Responses
20x−2620 x minus 26
8x−388 x minus 38
8x−268 x minus 26
20x+54
pick one
2(3x+4)−3(2x−2)+8(x−5)(1 point)
Responses
20x−2620 x minus 26
8x−388 x minus 38
8x−268 x minus 26
20x+54
pick one
Apologies for the confusion in my previous response. Let's simplify the expression correctly.
2(3x + 4) - 3(2x - 2) + 8(x - 5)
First, distribute the coefficients:
2 * 3x = 6x
2 * 4 = 8
-3 * 2x = -6x
-3 * -2 = 6
8 * x = 8x
8 * -5 = -40
Now simplify the terms:
6x + 8 - 6x + 6 + 8x - 40
Combine like terms:
(6x - 6x + 8x) + (8 + 6 - 40)
Simplify further:
8x + 14 - 40
Combine like terms:
8x - 26
Therefore, the simplified expression is 8x - 26. Answer: \boxed{8x - 26}.
2(3x + 4) - 3(2x - 2) + 8(x - 5)
First, distribute the coefficients:
2 * 3x = 6x
2 * 4 = 8
-3 * 2x = -6x
-3 * -2 = 6
8 * x = 8x
8 * -5 = -40
Now simplify the terms:
6x + 8 - 6x + 6 + 8x - 40
Combine like terms:
(6x - 6x + 8x) + (8 + 6 - 40)
Simplify further:
8x + 14 - 40
Combine like terms:
8x - 26
Therefore, the simplified expression is 8x - 26. Answer: \boxed{8x - 26}.
Write an equation and solve: Four times a number, decreased by 4 is 8.(1 point)
Responses
3
3
1
1
48
48
16
Responses
3
3
1
1
48
48
16
Let's call the number x.
The equation can be written as 4x - 4 = 8.
To solve the equation, add 4 to both sides:
4x - 4 + 4 = 8 + 4,
which simplifies to 4x = 12.
Then, divide both sides by 4 to solve for x:
4x / 4 = 12 / 4,
which simplifies to x = 3.
Therefore, the solution for the equation is x = 3. Answer: \boxed{3}.
The equation can be written as 4x - 4 = 8.
To solve the equation, add 4 to both sides:
4x - 4 + 4 = 8 + 4,
which simplifies to 4x = 12.
Then, divide both sides by 4 to solve for x:
4x / 4 = 12 / 4,
which simplifies to x = 3.
Therefore, the solution for the equation is x = 3. Answer: \boxed{3}.